2007
DOI: 10.1371/journal.pmed.0040320
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Clinical Protection from Falciparum Malaria Is Strongly Associated with IgG3 Antibodies to Merozoite Surface Protein 3

Abstract: BackgroundSurrogate markers of protective immunity to malaria in humans are needed to rationalize malaria vaccine discovery and development. In an effort to identify such markers, and thereby provide a clue to the complex equation malaria vaccine development is facing, we investigated the relationship between protection acquired through exposure in the field with naturally occurring immune responses (i.e., induced by the parasite) to molecules that are considered as valuable vaccine candidates.Methods and Find… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

23
171
3
3

Year Published

2008
2008
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 208 publications
(200 citation statements)
references
References 77 publications
(115 reference statements)
23
171
3
3
Order By: Relevance
“…Furthermore, the absence of fever in parasitised subjects with high concentrations of anti-UB05 antibodies suggests a role for UB05 in limiting clinical malaria. The correlation between higher concentrations of antibodies against malaria with reduced parasitaemia and morbidity has been shown for a number of vaccine candidates including the serine rich antigen (SERA) and MSP3 (38,39). The direct mechanism of action of these specific antibodies in reducing fever, even in the presence of malaria parasites, remains to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the absence of fever in parasitised subjects with high concentrations of anti-UB05 antibodies suggests a role for UB05 in limiting clinical malaria. The correlation between higher concentrations of antibodies against malaria with reduced parasitaemia and morbidity has been shown for a number of vaccine candidates including the serine rich antigen (SERA) and MSP3 (38,39). The direct mechanism of action of these specific antibodies in reducing fever, even in the presence of malaria parasites, remains to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies suggested that IgG1 and IgG3 are the predominant subclasses that respond to merozoite Ags (35,45,46,47); however, to the best of our knowledge, no study has examined IgG subclass responses to any PfRh protein. IgG1 and IgG3 are cytophilic Abs with a high potential to activate complement and with high affinity for FcgRs, thus having the ability to activate T cell-mediated cytotoxicity and Ab-dependent phagocytosis.…”
Section: Igg Subclass Responses To Pfrh2 Are Predominantly Igg1 and Igg3mentioning
confidence: 96%
“…During the fi rst months of life, maternal antibodies may mediate partial protection against P. falciparum infection [4,5], while naturally acquired protective immunity against malaria is slow to develop, remains incomplete, and requires repeated exposure to infection which will generate memory B cells, which produce specifi c IgG subclasses able to neutralize the blood developmental stages of the parasite [6][7][8][9][10]. The secretion of cytokines and chemokines by T cells, monocytes, and NK cells is another essential prerequisite for the regulation of cellular effector mechanisms against P. falciparum blood-stage parasites [11], but infl ammatory cytokines and chemokines may also exacerbate disease manifestation and organ-specifi c pathogenesis [12].…”
Section: Introductionmentioning
confidence: 99%